2010
DOI: 10.1080/13803391003672305
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Arabic normative data of neuropsychological tests: The verbal and design fluency

Abstract: This pattern is congruent with that reported in the western literature. The implications of these results in relation to the development of Arabic norms were discussed. It was concluded that these tests could be used in an Arabic-speaking population with due considerations to the effects of age and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 57 publications
(114 reference statements)
1
35
0
5
Order By: Relevance
“…Variable effects of sex on VF performance have been reported: many studies have failed to find significant sex differences [42, 60, 70], while others have found that women have superior performance [62, 69, 71]. Sex differences are further complicated by the different familiarity of men and women with particular semantic categories.…”
Section: Experiments 1 Demographic Influences On Verbal Fluencymentioning
confidence: 99%
“…Variable effects of sex on VF performance have been reported: many studies have failed to find significant sex differences [42, 60, 70], while others have found that women have superior performance [62, 69, 71]. Sex differences are further complicated by the different familiarity of men and women with particular semantic categories.…”
Section: Experiments 1 Demographic Influences On Verbal Fluencymentioning
confidence: 99%
“…In other languages, different combinations of letters are used to assess phonological fluency in more culturally-appropriate ways. For example, one Arabic study tested the use of W, R, and G, and found that these letters are more appropriate for use within an Arabic population (Khalil, 2010). Similarly, a Greek study used X (Chi), (Sigma), and A (Alpha) because these letters followed the same ratios as F, A, and S in the English language and were more relevant to the Greek alphabet and overall culture (Kosmidis, Vlahou, Panagiotaki, & Kiosseoglou, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Stricks et al (2008) collected normative data in Spanish from Spanish-speakers in the United States. Few norms studies on phonological fluency have been conducted in regions outside of the United States and Canada, including Sweden (Tallberg, Ivachova, Jones Tinghag, &Österberg, 2008), Saudi Arabia (Khalil, 2010), and the Netherlands (Van der Elst, Van Boxtel, Van Breukelen, & Jolles, 2006). Semantic fluency norms have also been established for animals, vegetables, fruits, foods, and clothing, primarily from the United States and Canada (Gladsjo et al, 1999;Lucas et al, 1998;Mitrushina, 2005;Tombaugh et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Khalil (2010) examined the performance of healthy Arabic-speaking adults in Saudi Arabia on verbal fluency tests. Both studies used the Arabic version of the semantic (i.e., naming as many animals as possible) and phonemic (i.e., reciting as many words that start with a certain sound) versions of this test.…”
Section: Introductionmentioning
confidence: 99%